2019
DOI: 10.1128/mbio.02155-19
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Suppression of Interferon Lambda Receptor Expression Leads to Enhanced Human Norovirus Replication In Vitro

Abstract: Human norovirus (HuNoV) is the main cause of gastroenteritis worldwide, yet no therapeutics are currently available. Here, we utilize a human norovirus replicon in human gastric tumor (HGT) cells to identify host factors involved in promoting or inhibiting HuNoV replication. We observed that an interferon (IFN)-cured population of replicon-harboring HGT cells (HGT-Cured) was enhanced in their ability to replicate transfected HuNoV RNA compared to parental HGT cells, suggesting that differential gene expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Before the discovery of the HIE-based HuNoV ex vivo culture system, innate immune responses to HuNoV RNA replication were examined by using human hepatoma (HG23) or gastric tumor (HGT) cell-based GI.1 replicon systems (31,49,50), and human embryonic kidney (293FT) cells transfected with authentic GI.1 HuNoV RNA from stools of infected persons or RNA expressed from a reverse genetics full-length GII.3 plasmid (30). The main limitation to these previous studies is that none represented a complete virus infection cycle; in particular, the viral entry step was missing, which itself can induce innate responses, and the sites of RNA replication may have been in cytoplasmic compartments different from those in an authentic viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Before the discovery of the HIE-based HuNoV ex vivo culture system, innate immune responses to HuNoV RNA replication were examined by using human hepatoma (HG23) or gastric tumor (HGT) cell-based GI.1 replicon systems (31,49,50), and human embryonic kidney (293FT) cells transfected with authentic GI.1 HuNoV RNA from stools of infected persons or RNA expressed from a reverse genetics full-length GII.3 plasmid (30). The main limitation to these previous studies is that none represented a complete virus infection cycle; in particular, the viral entry step was missing, which itself can induce innate responses, and the sites of RNA replication may have been in cytoplasmic compartments different from those in an authentic viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this also potentially explains the discrepancy between in vivo and in vitro results from studies on IFN responses to the human norovirus. For example, studies in Huh7 and 293FT cells have shown no IFN responses to HuNoV [51,52], while human challenge studies [53], studies in animal models [54,55], and in vitro studies in organoids [56][57][58], and replicon-containing cell lines [31] have all demonstrated induction of IFNs following infection. Given that both Huh7 and 293FT cells have impaired cGAS-STING pathways [29,59,60], our data demonstrating a role of this pathway in restriction of noroviruses harmonises these various otherwise conflicting data.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we wanted to see if there is a similar role for STING in the IFN responses against human noroviruses. For this, we made use of the recently described HGT-NV cells [31], a human gastric tumour cell line stably harbouring a GI.I human norovirus replicon. The cells were treated with DMSO or indicated doses of H-151, harvested 24 hours post treatment and subjected to RT-qPCR.…”
Section: Small-molecule Inhibition Of Sting Activation Enhances Replication Of Noroviruses In Cell Lines and Primary Cellsmentioning
confidence: 99%
“…IFN type I and II were shown to have an impact on NoV infections by triggering the host innate immune response [ 153 , 154 , 155 ]. Also type III IFN (IFN λ) was shown to protect mice against MNV challenge, therefore this could be explored for the treatment/prophylaxis of NoV infections [ 156 , 157 ].…”
Section: Antiviral Targets and Known Antiviralsmentioning
confidence: 99%